TINGKAT ADOPSI ARTIKEL TOPIK DAN EFEK KOMUNIKASI MAJALAH PERTANIAN Levels of Adoption Articles Topic ad Communication Effects of Agricultural Magazine - Sardi Duryatmo (Universitas Pakuan, 2018)
AbstractSardi DuryatmoThe mass media in developing countries has a large role to support development. Development will work faster if supported by mass media. The mass media creates awareness, provides informations, and direct informations for the purposes of educations and extensions. According to the diffusion of innovations theory, communicator who obtains meassage to the mass media, likely to have stronger influence towards others. The purpose of this study is to determine to level s of adoption of articles Topic among Trubus Magazine readers in South Jakarta, in order to know the effect the levels of adoption of innovation toward Trubus Magazine readers. Based on the data of Distribution Department Trubus Magazine, there are 308 readers in South Jakarta until Februarry2011. The samples of this study are 76 readers. The data was collected by quetionnaires and interviews: (1) an overwiew the characteristic of respondents, (2) the exposurse of Topic of Trubus Magazine, (3) communication effect associated of cognitive, affective affect, and behavioral effect, (4) adoption of innovation levels. Data analysis and processing characteristic of the relationshif using Spearman correlation formula. The results showed that (1) the distribution of respondents according to observable characteristics seems to vary, (2) top the three commodities on seven other which are prefered by respondents as a topic are fruit (18%), traditional medicines (15,7%), and plantation (14,7%), (3) in relation to cognitive effecets, the knowledge respsondents are increased. Likewise the affective affect, respondents are better, (4) the most widely adopted innovation by respondents is the biopori technology one of the methodes applied in rain water harvesting, (5) There is relation between exposure and knowledge and attitude.Key words: adoptions innovation, mass media